2022
DOI: 10.3390/molecules27196630
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermodynamic Thermal Properties of Quercetin and Similar Pharmaceuticals

Abstract: The thermodynamic properties of pharmaceuticals are of major importance since they are involved in drug design, processing, optimization and modelling. In this study, a long-standing confusion regarding the thermodynamic properties of flavonoids and similar pharmaceuticals is recognized and clarified. As a case study, the thermal behavior of quercetin is examined with various techniques. It is shown that quercetin does not exhibit glass transition nor a melting point, but on the contrary, it does exhibit vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…Almost simultaneously with the above mentioned studies regarding polymers, the thermochemical transition was also reported to occur in some low molecular weight substances, namely two flavonoids (silybin [ 15 ] and quercetin [ 16 ]) and gallic acid [ 17 ]. It was reported [ 16 ] that the thermochemical transition is the “connection” among three different aspects [ 16 ].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Almost simultaneously with the above mentioned studies regarding polymers, the thermochemical transition was also reported to occur in some low molecular weight substances, namely two flavonoids (silybin [ 15 ] and quercetin [ 16 ]) and gallic acid [ 17 ]. It was reported [ 16 ] that the thermochemical transition is the “connection” among three different aspects [ 16 ].…”
Section: Introductionmentioning
confidence: 94%
“…Almost simultaneously with the above mentioned studies regarding polymers, the thermochemical transition was also reported to occur in some low molecular weight substances, namely two flavonoids (silybin [ 15 ] and quercetin [ 16 ]) and gallic acid [ 17 ]. It was reported [ 16 ] that the thermochemical transition is the “connection” among three different aspects [ 16 ]. These three aspects are: (1) the inconsistencies detectable in the literature regarding the experimental values of the thermal thermodynamic properties of such (pharmaceutical) substances [ 15 , 16 , 17 ]; (2) the reported difficulty and poor efficiency of predicting the melting point of pharmaceuticals [ 18 , 19 ]; (3) the fact that Bawn kinetics has been applied to study pharmaceuticals [ 2 ].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations